1989
DOI: 10.1111/j.1571-9979.1989.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Resolution Training Programs: Implications for Theory and Research

Abstract: Interest in methods of conflict resolution has grown significantly in the last decade (Pruitt and Kressel, t985). Some of the more prominent developments include the emergence of public sector labor mediation, family and divorce mediation, and judicial and public resource mediation. This interest is also reflected in the number of courses included in the curricula of schools of law and business, graduate programs in sociology and social psychology, and in inter-disciplinary programs focusing on conflict resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Simulations provide the instructor with the opportunity to combine teaching of theory with students actually practicing with various behaviours (Lewicki, 1986). However, Schultz (1989) is critical of most negotiation training programs for not basing their instruction on the well-established body of theory on the subject. Simulations allow participants to experiment with various negotiation styles and techniques, and to receive feedback from others in a low-risk environment where there is no actual dispute or any relationships at stake (Lewicki, 1986).…”
Section: Use Of Simulations In Teaching Negotiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations provide the instructor with the opportunity to combine teaching of theory with students actually practicing with various behaviours (Lewicki, 1986). However, Schultz (1989) is critical of most negotiation training programs for not basing their instruction on the well-established body of theory on the subject. Simulations allow participants to experiment with various negotiation styles and techniques, and to receive feedback from others in a low-risk environment where there is no actual dispute or any relationships at stake (Lewicki, 1986).…”
Section: Use Of Simulations In Teaching Negotiationmentioning
confidence: 99%
“…A search of the literature for evaluations of negotiation role-playing simulations revealed a single example. Schultz (1989) studied four negotiation training programs (throughout North America), and found that none monitored the extent to which the graduates were effective conflict resolvers. All measured the success of their program solely on the basis of questionnaires completed by students immediately on completion of the course, in which the success of the simulation was measured only by the students' satisfaction with the course.…”
Section: Use Of Simulations In Teaching Negotiationmentioning
confidence: 99%
“…Los programas de formación con frecuencia emplean encuestas de opinión para determinar la satisfacción del participante con el curso de negociación. La mayoría de las veces, los participantes reportan un alto grado de satisfacción con la capacitación recibida, sin embargo, pocos programas evalúan si realmente la capacitación aumenta los conocimientos de los participantes o el mejoramiento de sus habilidades de negociación (Schultz, 1989)…”
Section: Objetivos Específicosunclassified